Geography, climate change, national security : the case of the evolving US arctic strategy - Lavorio A. (The International Spectator, 2021)
The US is showing ever greater attention to the Arctic as a result of the geopolitical incentives and constraints deriving from climate change–an abrupt change in physical geography. According to major defence documents, the effects of climate change on US national security have intensified in the last few years, threatening even homeland defence. The very fact that the consequences of climate change have been taken into consideration by the Trump administration’s national security planning despite the President’s controversial position on global warming constitutes remarkable proof of the persistent importance of geography for national security.